INDONESIA DALAM DINAMIKA HUKUM INTERNASIONAL DI ASEAN - Prasetya Putra Nugraha (JOURNAL OF LAW AND NATION, 2026)
Southeast Asia is a region that has very dynamic conditions both in the political, economic and socio-cultural fields, so this has an impact on clasch of national interest in each country. Indonesia as the leader of ASEAN has a major role as the “motorof ASEAN’ one of whose important roles is active involvement in handling international legal issues in the Southeast Asian region. The purpose of this study is to analyzing Indonesia’s strategic role in his involvement in handling the dynamics of international law in ASEAN. The research methhod used is literature study by reading, collecting then analyze the literature that has been obtained. The research result show that Indonesia’s important role is not only actively involved in addressing international legal issues in ASEAN but also has a big influence in maintaining defense and security stability in the region by taking advantage of geopolitical position. Besides that, Indonesia has a central role in mediating conflicts between ASEAN members. As leader of ASEAN Indonesia’s existence is very decisive stability conditions in the Southeast Asia region.